"From taboo to routine": a qualitative evaluation of a hospital-based advocacy intervention for domestic violence and abuse - Sandi Dheensa; Gemma Halliwell; Jennifer Daw; Sue K. Jones; Gene Feder (BMC, 2020)
Abstract Background Health services are often the first point of professional contact for people who have experienced domestic violence and abuse. We report on the evaluation of a multi-site, hospital-based advocacy intervention for survivors of domestic violence and abuse. Independent Domestic Violence Advisors (IDVAs), who provide survivors with support around safety, criminal justice, and health and wellbeing, were located in five hospitals in England between 2012 and 2015 in emergency departments and maternity services. We present views about IDVAs' approaches to tackling domestic violence and abuse, how the IDVA service worked in practice, and factors that hindered and facilitated engagement with survivors. Methods We adopted a convenience sampling approach and invited participation from all who offered to take part within the study timeframe. Sixty-four healthcare professionals, IDVAs, IDVA service managers, and commissioners at all sites were interviewed. Interviews were analysed using a thematic approach: familiarising ourselves with the data through repeated readings and noting initial ideas; generating initial codes through double coding notable features of the data across the dataset; collating codes into potential themes; and reviewing themes to ensure they captured the essence of the data. Results Two key themes emerged. The first was Hospital-based IDVAs fulfil several crucial roles. This theme highlighted that healthcare professionals thought the hospital-based IDVA service was valuable because it enhanced their skills, knowledge, and confidence in asking about domestic violence and abuse. It enabled them to immediately refer and provide support to patients who might have otherwise been lost along a referral pathway. It also reached survivors who might otherwise have remained hidden. The second theme was Success hinges on a range of structural factors. This theme illustrated the importance of ongoing domestic violence and abuse training for staff, the IDVA having private and dedicated space, and the service being embedded in hospital infrastructure (e.g. featuring it in hospital-wide policies and enabling IDVAs access to medical records). Conclusion Hospital-based IDVAs offer a unique and valued way to respond to domestic violence and abuse in a healthcare setting. Further work must now be done to explore how to implement the service sustainably.